Fertility Response Following Estradoublesynch and Progesterone Based Ovsynch Protocols in Delayed Pubertal Buffalo Heifers - Pothireddy, Suresh K.; Honparkhe, Mrigank; Ahuja, Ankit Kumar; Dhindsa, Shahbaz Singh; Singh, Prahlad (The Indian Journal of Animal Reproduction, 2022)
The study evaluated the fertility response following Estradoublesynch and progesterone-based Ovsynch protocols in delayed pubertal buffalo heifers. A total of twenty delayed pubertal buffalo heifers were subdivided in two equal subgroups. Group I animals were treated with PGF2α analogue (500 µg cloprostenol sodium) i.m. on day 0, GnRH analogue (20 µg buserelin acetate) on day 2, PGF2α analogue (500 µg cloprostenol sodium) repeated on day 9 and estradiol benzoate 1 mg intramuscular (i.m.) on day 10. Fixed-time artificial insemination (FTAI) was done at 48 and 60h. Group II animals were subjected to GnRH analogue (20 µg buserelin acetate) i.m. along with CIDR insert intravaginally on day 0, PGF2α analogue (500 µg cloprostenol sodium) i.m. and removal of CIDR on day 7, GnRH analogue on day 9 followed by FTAI at 12 and 24h. Blood collection (plasma P4) and ultrasonography (luteal and follicular dynamics) was performed on day 0, 9, 10, 12 in group I and day 0, 7, 9 and 10 in group II animals. Pregnancy diagnosis was made at 45-60 days post AI. Estrus response was observed in all the buffalo heifers of group I and II. First service conception rate was significantly higher in group I (50%) compared to group II (20%) (P<0.05). Overall pregnancy rate was almost similar in both group I and II (60% vs 70%). In conclusion, estradoublesynch and progesterone-based ovsynch protocol can effectively induce ovulatory estrus and improve pregnancy rates in delayed pubertal buffalo heifers.